Heat Transfer And Deformation Of Flexible Printed Circuit Board With Multi Ball Grid Array Packages - Lim, Chong Hooi (2017)
The rapid development of electronic and microelectronic technology increases the demands for electronics device with flexible and light weight capability. Flexible printed circuit board (FPCB) which can be used to replace rigid printed circuit board (RPCB) is well equipped with those features. However, the soft feature of FPCB poses unwanted deflection (δ) and stress from the flow and heat generated by the operating components. In present research, thermal and flow effects on FPCB with attached ball grid array (BGA) packages have been investigated where the numerical simulation with coupled of flow and thermal effects concurrently has been successfully developed in the simulation. The effects of flow are studied at the initial stage of the research, followed by the addition of heat source to the BGA packages. The experimental work with actual attached ball grid array (BGA) packages was carried out to verify and validate the results. Findings show that better heat transfer performance on FPCB with an average 24 % higher than RPCB. Several parametric factors are explored including flow velocities (v) (1 – 5 m/s), 1 - 4 number of BGA packages attached, power supplied to the BGA packages (0 – 0.213 W), size of FPCB (80mm2 – 140mm2) and distance between BGA packages (15 mm – 45 mm). The heat transfer coefficient (h) has been added into the responses to study the heat transfer in the cases that involved heat source. Later on, v, δ and h had been normalized into dimensionless Reynolds number (Re), δ/length of FPCB (L) and Nusselt number (